Correction: The corrosion behaviors of multilayer diamond-like carbon coatings: influence of deposition periods and corrosive medium. Issue 58 (19th November 2021) - Cui, Mingjun; Pu, Jibin; Zhang, Guangan; Wang, Liping; Xue, Qunji
Abstract : Correction for 'The corrosion behaviors of multilayer diamond-like carbon coatings: influence of deposition periods and corrosive medium' by Mingjun Cui et al., RSC Adv., 2016, 6, 28570–28578, DOI: ; 10.1039/C6RA05527C .